Pembinaan Disiplin Guru untuk Peningkatan Prestasi Kerja melalui Supervisi Akademik di SDN Teluk Tiram 2 Banjarmasin - Norjenah (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
The teacher role in the learning process at schools can’t be separated forom amongst non permanent teachers in carrying out tasks. Discipline play significant roles for education, used especially fot motivate teachers to be able to discipline ourselves and to be able to reach work pperformance in carrying out teaching, either individually as well as groups. Lack of teachers who have high will be still working well albeit without supervised by a superior. For developing discipline teachers works to improve performance through supervision at the SDN Teluk Tiram 2 Banjarmasin. Methods used in research action this school research reduce class action. The result showed that through supervision academic implemented for three cycle conducted by the school principal, teachers work discipline increased. The observation made among others : 1) the accuracy of the presence of the teachers at the school 2) the availability of a device of learning 3) teacher attendance at class 4) the use of time learning in class 5) out of teachers in class 6) timeliness in the resolution of a task assigned as well as 7) return the accuracy of teachers from schools. The research was conducted for three cycles, and was based on the results of the analysis on each cycle show discipline on teacher performance is likely to increase on each other indicators, both in number and the percentage of any cycle next year can be achieved and full fill the success of indicators of 90%. Is a direct influence on increased work performance teachers in SDN Teluk Tiram 2 Banjarmasin in meaning development work ethic with working through academic discipline supervision done by the school principal. Hence, when supervision be raised it work school principals discipline was also increase.